2006
DOI: 10.1088/1742-6596/36/1/015
|View full text |Cite
|
Sign up to set email alerts
|

General entanglement

Abstract: The paper contains a brief review of an approach to quantum entanglement based on analysis of dynamic symmetry of systems and quantum uncertainties, accompanying the measurement of mean value of certain basic observables. The latter are defined in terms of the orthogonal basis of Lie algebra, corresponding to the dynamic symmetry group. We discuss the relativity of entanglement with respect to the choice of basic observables and a way of stabilization of robust entanglement in physical systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 46 publications
1
59
0
Order By: Relevance
“…As a matter of fact, violation of Bell-type conditions indicates the absence of hidden classical variables in quantum mechanics rather than entanglement. This allows us to conclude that nonlocality and violation of classical realism alone are not the essential sign of entanglement and that there is no physical prohibition for the existence of entanglement of local objects (particles) caused by quantum correlations of their intrinsic degrees of freedom [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…As a matter of fact, violation of Bell-type conditions indicates the absence of hidden classical variables in quantum mechanics rather than entanglement. This allows us to conclude that nonlocality and violation of classical realism alone are not the essential sign of entanglement and that there is no physical prohibition for the existence of entanglement of local objects (particles) caused by quantum correlations of their intrinsic degrees of freedom [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 95%
“…This notion does not contain any quantification of distance between separated entangled parts of a quantum system. Thus, it seems to be natural to assume that quantum system with strongly correlated intrinsic parts may manifest entanglement independent of distance between the parts and hence even as a local object without spatial separation of parts [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was found that the spin squeezing is closely related to quantum entanglement [17][18][19][20][21][22], which plays an important role in quantum information and quantum computation. For an ensemble of two-level system, spin squeezing implies entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…For an ensemble of two-level system, spin squeezing implies entanglement. At the same time, it was shown that a single spin-like system with S greater than 1/2 can also manifest entanglement [19][20][21], moreover, the single- * …”
mentioning
confidence: 99%